The effectiveness of beach mega-nourishment, assessed over three management epochs. (15th December 2016) - Brown, Jennifer M.; Phelps, Jack J.C.; Barkwith, Andrew; Hurst, Martin D.; Ellis, Michael A.; Plater, Andrew J.
Abstract: Resilient coastal protection requires adaptive management strategies that build with nature to maintain long-term sustainability. With increasing pressures on shorelines from urbanisation, industrial growth, sea-level rise and changing storm climates soft approaches to coastal management are implemented to support natural habitats and maintain healthy coastal ecosystems. The impact of a beach mega-nourishment along a frontage of interactive natural and engineered systems that incorporate soft and hard defences is explored. A coastal evolution model is applied to simulate the impact of different hypothetical mega-nourishment interventions to assess their impacts' over 3 shoreline management planning epochs: present-day (0–20 years), medium-term (20–50 years) and long-term (50–100 years). The impacts of the smaller interventions when appropriately positioned are found to be as effective as larger schemes, thus making them more cost-effective for present-day management. Over time the benefit from larger interventions becomes more noticeable, with multi-location schemes requiring a smaller initial nourishment to achieve at least the same benefit as that of a single-location scheme. While the longer-term impact of larger schemes reduces erosion across a frontage the short-term impact down drift of the scheme can lead to an increase in erosion as the natural sediment drift becomes interrupted. This research presents a transferable modelling tool to assess the impact of nourishment schemes for a variety of sedimentary shorelines and highlights both the positive and negative impact of beach mega-nourishment. Highlights: Exploratory impact modelling of different beach mega-nourishment schemes over 20, 50 and 100 years. Shoreline response, assessed over time and space, to different beach nourishment options. Demonstration of a modelling tool to assess management options for different shoreline types.